Try not to breathe - Bell, David, 1969 November 17- (Berkley, 2023)
"An ex-cop sets out to find her missing sister and discovers the horrifying truth about her family... A traumatic experience in the line of duty forces thirty-year-old Avery Rogers to abandon both her relationship and her position as a Kentucky State Police officer. She retreats to a college town where she works an unfulfilling job as a security guard, breaking up fights between drunken frat boys. But a frantic phone call turns Avery's life upside down. Her father-a retired cop who never fails to convey his disappointment in Avery-says her half sister is missing and in danger. Avery is sure Anna's just crashing with friends, but her father strong-arms her into searching for the sister she barely knows. Anna Rogers is fed up with her family-a half sister who resents her existence and a domineering father who thinks it's okay for cops to shoot unarmed civilians. She hits the road to attend a protest against police brutality, unaware of the danger that awaits her there. Just after catching a glimpse of Avery at the protest, Anna receives a shocking text. Now she's no longer road-tripping; she's running, pursued by an older sister she doesn't trust and a violent stranger who has been stalking her for weeks. When Avery discovers Anna's hiding place near a remote cave system, she risks everything to save her. Little do the sisters know that the past is catching up with them-including the explosive secret at the very heart of the Rogers family"--